The reality of the use of the Internet in the process of learning among a sample of students of the universities of Kerbala and Kufa: واقع استخدام شبكة الإنترنت في عملية التعلّم لدى عينة من طلبة جامعتي كربلاء والكوفة - Zinah Abdulridha Abu Tiheen, Asraa Hussien Abdul Ameer (Journal of engineering sciences and information technology, 2019)
In recent years، we have witnessed the revolution of technology in all sides of life. Therefore، education has been used to exploit this revolution and everyone has the opportunity to benefit from it in the learning. Education at this time has become both electronic and traditional. The educational seeks to achieve many results that keep pace with the times. This study aimed at revealing the extent of the use of technology in the learning for students of the Faculty of Science / Karbala University and the Faculty of Education for Girls / Kufa University in all departments (Computer، Chemistry، Physics، Biology، Mathematics، Sports، Geography، History، Arabic) by electronic questionnaire aimed to comparison between students of humanities study and scientific study in the use of the Internet، comparison of the most sites (YouTube، Google، Facebook،…) that used by students، know number of hours spent by learners in the use of the Internet in the learning process، and stand on the reasons not to use the Internet in the self-learning. This article showed that the number of Internet scientific study students in learning exceeded the number of human study students who do not use the Internet in learning.